Komunitas Virtual dan Riil: Relasi Gereja dan Media Sosial di Era Digital - Nole, Otniel Aurelius; Benu, Juliantri Mayangsari; Ruhukail, Joi Niagara Junior; Radja Hedo, Dylan Azarya; Delahoya, Samuel (Sekolah Tinggi Teologi Sriwijaya, 2024)
The church stands by the conditions of natural communities. Nevertheless, the church in history must accept that technology is also present. In this case, the church must make technology a companion, not an opposition. The church works with technology, one of which produces communities on social media. This research used the theory of Tim Hutchings and Irwyn L. Ince Jr. on ecclesiology. This research aimed to analyze virtual communities in the online world and natural communities in the offline world as different needs by revealing the closeness of the church and social media in the digital era. The method was qualitative research with a literature review and observation. The researchers found that the relationship between the church and social media in the digital era is not a big problem as long as people understand their priorities and conditions, namely setting themselves into virtual communities as secondary needs and natural communities as primary needs.